INTEGRASI KERJA OTAK DALAM PROSES PENDIDIKAN DAN BELAJAR - Syafriyon; Dahlan, Dasrizal; Lahmi, Ahmad; Hakim, Rosniati (LPPM STAI Muhammadiyah Probolinggo, 2025)
The brain is integrated in the education and learning process because the brain is the center for storing knowledge. The brain has a role as a control center for various body functions and mental processes. The brain plays a key role in how we obtain, process and store information. Among the brain's roles in education and learning: as an information processing center. When we learn, the brain receives data through the senses (sight, hearing, etc.), then processes the information, stores it in memory, and allows us to access it when needed. This process involves various areas of the brain, such as the prefrontal cortex (for planning and decision making) and the hippocampus (for memory formation). The brain allows us to learn through experience and repetition. This process involves structural changes in the brain called neuroplasticity, in which connections between nerve cells are strengthened or made new. Our brains are involved in decision making and problem solving during the learning process. When we are faced with a new task or problem, the brain analyzes the information, makes judgments, and chooses the most appropriate solution.Effective education depends on our understanding of how the brain works in learning and how we can create an environment that supports optimal cognitive development. This research aims to look at the role of the brain in the education and learning process more deeply, so the method used is qualitative, namely researching a problem in depth, collecting and analyzing non-numerical data such as reading texts, books, videos, bulletins and so on.